Assessment of intraoperative and postoperative complications during implementation of laparoscopic radical prostatectomy in patients with locally advanced prostate cancer - Cieśliński, Piotr; Hojan-Osicka, Małgorzata; Antczak, Andrzej; Kwias, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2011)
Aim of the study : This paper presents our personal experience in performing laparoscopic radical prostatectomy (LRP) at our institution. Material and methods : Within less than two years, i.e. from November 2008 to August 2010, 30 laparoscopic radical prostatectomies were performed at the Department of Urology and Uro-Oncology in Poznań. The operations were performed with the retroperitoneal approach. Lymphadenectomy was performed only in the patients with a preoperative prostate specific antigen (PSA) level greater than 10 ng/ml and/or Gleason score 7 or greater. Results: The operating time ranged from 150 to 360 minutes (mean operating time was 234 minutes). Two cases required conversion to open surgery because of highly increased prostate volume (100 ml) and due to difficult operating conditions. During one of the very first procedures rectal injury occurred and the patient developed a rectourethral fistula two weeks after surgery. Six patients had a prolonged drain leakage (> 7 days) caused by dehiscence of the vesicourethral anastomosis. One patient developed a large abdominal wall haematoma in the right and left lumbar region which was successfully treated with conservative management. One patient presented haematuria which stopped spontaneously on the 10 th postoperative day. On the first post-operative days 5 patients developed a fever which lasted a few days. Conclusions: An increasing number of urology clinics and hospitals perform laparoscopic radical prostatectomy. This ablative and reconstructive surgery is a technically challenging procedure and can be successfully performed by a urological team experienced in laparoscopy and radical prostatectomy. The procedure requires consistent improvement of the operative technique in order to provide patients with the most satisfactory oncological and functional results. The complication rate for all 30 patients undergoing the operation was low and complications were more frequent in initial cases.